2016
DOI: 10.1016/j.jmii.2014.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Bacteremic pneumonia caused by extended-spectrum beta-lactamase-producing Escherichia coli and Klebsiella pneumoniae: Appropriateness of empirical treatment matters

Abstract: ESBL-producing bacteremic pneumonia, especially health-care-associated infections, often occurred in adults with comorbidities. Appropriate empirical therapy was associated with a favorable outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 35 publications
2
30
1
2
Order By: Relevance
“…One study was multicenter and performed in 12 countries (Table 1) [15], 6 studies were performed in the Western Pacific region (4 in China [2 of them were performed in Taiwan], 1 in Republic of Korea, and 1 in Singapore) [16, 18, 21, 22, 24, 27], 4 studies were performed in the European region (1 in Italy, 2 in Spain, and 1 in Turkey) [20, 23, 26, 28], and 3 studies were performed in the region of the Americas (1 in Canada and 2 in United States of America) [17, 19, 25]. The isolated pathogens were Escherichia coli in 5 studies [16, 20, 23, 26, 27], Enterobacter cloacae in 2 studies [22, 25], E coli or Klebsiella pneumoniae in 5 studies [17–19, 21, 24], and E coli or K pneumoniae or Proteus mirabilis in 1 study [28].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study was multicenter and performed in 12 countries (Table 1) [15], 6 studies were performed in the Western Pacific region (4 in China [2 of them were performed in Taiwan], 1 in Republic of Korea, and 1 in Singapore) [16, 18, 21, 22, 24, 27], 4 studies were performed in the European region (1 in Italy, 2 in Spain, and 1 in Turkey) [20, 23, 26, 28], and 3 studies were performed in the region of the Americas (1 in Canada and 2 in United States of America) [17, 19, 25]. The isolated pathogens were Escherichia coli in 5 studies [16, 20, 23, 26, 27], Enterobacter cloacae in 2 studies [22, 25], E coli or Klebsiella pneumoniae in 5 studies [17–19, 21, 24], and E coli or K pneumoniae or Proteus mirabilis in 1 study [28].…”
Section: Resultsmentioning
confidence: 99%
“…The isolated pathogens were not specified in 1 study [15]. In addition, 8 studies reported mortality at 30 days [15, 16, 18, 20, 21, 24, 26, 27], 2 studies reported mortality at 28 days [22, 25], 1 study reported mortality at 21 days [28], 1 study reported mortality at 14 days [23], and 2 studies reported outcomes until hospital discharge [17, 19]. A summary of the number and percentage of patients with ESBL-PE BSI categorized according to the source of BSI is provided in the Supplementary Data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When availability of resources is low, capacity to reach these demands is limited. In a situation like ours where antimicrobial stewardship could not be achieved, we would expect survival in BSI to depend on two things: treatment that is started before severe organ failure has developed, and pathogens that are susceptible to the antibiotic that is given empirically [ 23 ]. It is a tragedy, of course, if empirical treatment commonly fails in settings where resistance cannot be identified in time.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies tried to investigate the potential impact of bacteremic pneumonia due to a worse outcome. However, clinical studies of bacteremic pneumonia caused by ESBL producers are limited [8].…”
Section: Fatal Hemorrhagic Bacteremic Escherichia Coli Pneumonia In Nmentioning
confidence: 99%